Mystery Box Media Increases Motivation and Learning Achievement of Fourth Grade Students in Civics Learning - Nuhaa, Faadiyah; Witanto, Yuli (Jurnal Penelitian dan Pengembangan Pendidikan, 2024)
Lack of use of interesting, creative, and diverse learning resources in the classroom can reduce students' motivation to learn, resulting in low student achievement. Therefore, this research aims to analyze the use of mystery box media on student motivation and learning achievement in Civics class IV elementary school subjects. This type of research uses a quasi-experimental approach in experimental quantitative research. The design of this research is an unequal control group design. The sample for this research was 25 experimental class students and 19 control class students. The data collection techniques are tests, questionnaires, documentation, observation, and interviews. Validity and reliability tests are used in the testing instrument. The data analysis techniques used are t-test, N-Gain, homogeneity test, normality test, and descriptive analysis. The research results showed that the experimental class's average post-test learning achievement score was more significant than the average post-test score for the control class. The t-test value shows differences in student learning outcomes after using mystery box media in the Civics class IV elementary school subject. In addition, the experimental group showed a higher learning motivation level than the control group. It was concluded that the application of mystery box media was significantly practical for students' learning motivation and achievement in class IV civics education (PPKn) in elementary school.